2014
DOI: 10.1056/nejmoa1401520
|View full text |Cite
|
Sign up to set email alerts
|

Rosuvastatin for Sepsis-Associated Acute Respiratory Distress Syndrome

Abstract: BACKGROUND In the acute respiratory distress syndrome (ARDS), inflammation in the lungs and other organs can cause life-threatening organ failure. Inhibitors of 3-hydroxy-3-methylglutaryl coenzyme A reductase (statins) can modulate inflammatory responses. Previous observational studies suggested that statins improved clinical outcomes in patients with sepsis. We hypothesized that rosuvastatin therapy would improve clinical outcomes in critically ill patients with sepsis-associated ARDS. METHODS We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
221
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(230 citation statements)
references
References 43 publications
7
221
1
1
Order By: Relevance
“…At randomisation, the tidal volume was 8.1 ml/kg of predicted body weight and it is possible that this level of tidal volume may have confounded the potential effects of simvastatin. However, this is unlikely given the similar absence of benefit for rosuvastatin in the SAILS study, 12 in which the mean tidal volume was 6.6-6.8 ml/kg of predicted body weight. Our data for tidal volume and plateau pressure are consistent with those seen in other clinical trials in critical care in which ventilation is not strictly protocolised.…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…At randomisation, the tidal volume was 8.1 ml/kg of predicted body weight and it is possible that this level of tidal volume may have confounded the potential effects of simvastatin. However, this is unlikely given the similar absence of benefit for rosuvastatin in the SAILS study, 12 in which the mean tidal volume was 6.6-6.8 ml/kg of predicted body weight. Our data for tidal volume and plateau pressure are consistent with those seen in other clinical trials in critical care in which ventilation is not strictly protocolised.…”
Section: Resultsmentioning
confidence: 96%
“…This was approximately 10 : 1 in this study, which is similar to other ARDS trials. 12 This represents a considerable workload and should be considered when setting up such trials. Surprisingly, the appropriate clinical outcome or set of clinical outcomes to use in a trial recruiting patients with ARDS requiring mechanical ventilation in ICU to date has not been defined.…”
Section: Economic Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…One randomized, double-blinded, placebo-controlled trial found that simvastatin was associated with improvements in non-pulmonary organ dysfunction in acute lung injury patients [142]. This said, enthusiasm for statins as potential acute lung injury therapeutics was recently reduced by the reporting of a large multicenter ARDS Clinical Trials Network study which found that rosuvastatin did not improve mortality or ventilator-free days and was instead associated with fewer days free of renal and hepatic failure [143]. …”
Section: A Role For Statins In Host Defense?mentioning
confidence: 99%
“…10 The SAILS trial randomised patients within 48 h of enrolment to receive either rosuvastatin or placebo for a maximum of 28 days (or until the third day after discharge from the intensive care unit (ICU), hospital discharge or death). The primary outcome of the original study was 60-day in-hospital mortality.…”
mentioning
confidence: 99%